Parliamentary scrutiny - an effective tool in reducing the perception of legitimacy and democratic deficit in the European Union - Elferte, Justīne Lība (Riga Graduate School of Law, 2018)
The European Union has democracy as one of its fundamental values but is often accused of having constant democratic deficit. The aim of this research is to identify the range of influence of national parliaments in a democratic European Union. In order to answer the research question the investigation will focus mostly on a national case study of the European Affairs Committee of the Latvian Parliament for which primarily a European context is needed. The European Union angle will be developed basing the research on the principles enshrined in the treaties, their protocols and interpretations. Additionally, scholarly research is to be critically consulted with the aim of reviewing the development of the concept of parliamentary scrutiny.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law